Analisis Activity Based Costing Dalam Menentukan Tarif Harga Jual Kamar Hotel Asa Larantuka - Pecking, Maria Winarti Sirapati; Tanusi, Gabriel; Sari, Santy Permata (SCIENTIFIC JOURNAL OF MANAGEMENT AND BUSINESS (SJMB), 2021)
The purpose of this research is to increase knowledge about determination of room selling price rates using activity based costing, can be used as a reference in setting the selling price rate a Hotel Asa Larantuka and as a comparison tool with the set selling pice so far, as well asa being one of the inputs that provide information regarding activity based costing, especially in its application to a hotel.The main orientation is service to the visitors. The analytical method used is a comparative analysis, which is an analysis that compares between the price of the Asa Larantuka Hotel room using the method traditional and activity based costing methods. The results of the study show that from the calculation of the room rate for selling the room by using activity based costing, when compared to tariffs used by Hotel Asa Larantuka, activity based costing gives smaller results for VIP rooms Rp 423.789/day/room. Deluxe double room for IDR 373.154/day/room, Deluxe twin room for Rp 380.614/day/room., for Boat room Rp 376.076/day/room, and for standard room Rp 350.054/day/room. For the price of the hotel room seliing price Asa Larantuka for VIP room is Rp 968.000/day/room, for room Deluxe double for IDR 484.000/day/room for Deluxe twin room for Rp 484.000/day/room, for Biat room Rp750.000/day/room, for standars room Rp 363.000/day/room.